Métodos de inoculação de Beauveria bassiana no percevejo Euschistus heros e compatibilidade com inseticidas químicos e adjuvantes - Stacke, Regina Sonete (2021)
The brown stink bug, Euschistus heros (Hemiptera: Pentatomidae), is the main pest of the soybean crop. Its control is carried out mainly with chemical insecticides, but in the last year products based on entomopathogenic fungi were registered for the management of this pest. However, the expansion of biological control of this pest still requires many studies. The objective of this work was to evaluate methods of inoculation of two isolates of Beauveria bassiana (UFSM 1 and UFSM 2) on the stink bug E. heros and to evaluate the compatibility of one of the isolate (UFSM 1) with different insecticides and adjuvants used for its control. Suspensions with 1x101, 1x103, 1x105, 1x107 e 1x109 conidia mL-1 of which UFSM 1 and UFSM 2 were applied to insects by dorsal contact, tarsal contact and immersion methods. The compatibility of the products with the UFSM 1 isolate was obtained based on vegetative growth and conidia production. The highest mortalities occurred in the highest concentration, which were for the UFSM 1 isolate of 91%, 66% and 58% for the immersion, dorsal contact and tarsal contact methods, respectively. For the UFSM 2 isolate, this mortality was 93%, 71% and 66%, respectively. The products Extremo®, IOP®, Spray Oil®, Engeo Pleno S®, Connect® and Fastac Duo® were considered compatible with the isolate UFSM 1, while the TA35 Gold® and Veget'Oil® products were considered toxic and moderately toxic, respectively. Dorsal contact and tarsal contact inoculation methods were similar in causing death of E. heros. UFSM 1 is compatible with six of the eight agrochemicals tested.